(untitled) (Scientific journal of the Fergana State University, 2023)
The article investigates the emergence of the poetic riddle genre in written literature, especially in children’s poetry under the influence of the riddle genre and folklore, its importance in the development of children’s thinking and mental potential, its poetic properties, and the acquisition of an educational, artistic and aesthetic essence. The analysis was carried out on the basis of innovative riddles by Tursunboy Adshboyev, Polat Momin and Abdurahman Akbar. In the creation of poetic riddles, followership and originality, stylistic skills and individuality of the creator are compared.